Invited Commentary: The Continuing Need for the Sufficient Cause Model Today - VanderWeele, Tyler J. (Am J Epidemiol, 2017)
In this commentary, I review the insights that have been gained using Rothman's sufficient cause model (Am J Epidemiol. 1976;104(6):587–592). Discussion pertains to the relations of the model to similar conceptualizations in other fields of study, the advances and extensions that have been made to the model since the paper's publication, and its relation to questions of actual causation, along with questions concerning the use of the model in the future of epidemiology.